Mapping studies of geodynamic processes (Journal of Geography and Environmental Management, 2019)
There are a number of different ways to study the characteristics of geodynamic processes - types, spatial distribution,dynamics of manifestation. Among them, the most affordable and at the same time, the most difficult, requiringgood professionalism, is the analysis and comparison of general and thematic maps of various scales. In this articleidentification questions endo-and ekzodinamical processes of a morphogenesis as a result of the analysis thematic(geological, tectonic, geomorphological) and topographic maps are considered.